Effects of soy protein and resistance exercise on body composition and blood lipids in postmenopausal women - Maesta, Nailza; Nahás, Eliana Aguiar Petri [UNESP]; Nahas-Neto, Jorge; Orsatti, Fabio L.; Fernandes, Cesar E.; Traiman, Paulo [UNESP]; Burini, Roberto Carlos [UNESP] (Elsevier B.V., 2007)
Objective: To assess the effect of soy protein and progressive resistance training on body composition and lipids in postmenopausal women.Design: In a controlled trial, 46 postmenopausal women were randomized to one of four groups: 25 g of soy protein (SP, n = 10), 25 g of soy protein plus resistance exercise (SPE, n = 14), 25 g of maltodextrine (placebo) (PL, n = 11), or placebo plus resistance exercise (PLE, n = 11). Progressive resistance training was held three times a week for 16 weeks and included 8 exercises (3 series of 8-12 repetitions). At baseline and after 16 weeks, body mass index, waist circumference (WC), body fat, muscle mass and serum lipid levels were measured. To confirm isoflavone absorption, urinary concentrations were determined. The t-test of Student and ANOVA were used in the statistical analysis.Results: Subjects were classified as overweight and showed android fat distribution: Urinary isoflavone excretion indicated compliance to soy protein treatment. After 16 weeks of intervention, both SPE and PLE groups showed a significant increase of 1.3 kg in muscle mass and reduction in WC of -1.4 and -2.1 cm, respectively (p < 0.05). Significant decreases in the mean values of total cholesterol and LDL (-29.0 and -24.0 mg/dL, p < 0.001 and p < 0.006, respectively) were observed in the users of soy protein alone (SP).Conclusions: Soy protein supplementation did not influence the indicators of body composition. However, it exerted possible favorable effects on lipid profile in postmenopausal women. The increase in muscle mass and reduction in abdominal fat were correlated with resistance training. (c) 2006 Elsevier B.V.. All rights reserved.
Keywords: soy protein; resistance exercises; body composition; lipids; menopause